AB1262 Relative contribution of tenosynovitis and joint synovitis in rheumatoid and psoriatic arthritis revealed by contrast-enhanced, dynamic MRI: Das 28 correlates with the extension of synovitis but not with its severity. (23rd January 2014) - Zampogna, G.; Barbieri, F.; Boesen, M.; Paparo, F.; Kubassova, O.; Parodi, M.; Cutolo, M.; Cimmino, M.A.
Abstract : Background: Dynamic, contrast-enhanced MRI (DCE-MRI), the quantification of enhancement within the synovial membrane and bone by extracting curves using fast T1-weighted sequences during intravenous administration of contrast agent, is useful to evaluate synovitis and bone marrow edema in arthritis. Objectives: In this pilot study, we looked at possible differences between joint synovitis and tenosynovitis in psoriatic arthritis (PsA) as compared with rheumatoid arthritis (RA). Methods: Seven patients with PsA and 10 with rheumatoid arthritis were studied. After DCE-MRI was performed on three axial slices of the wrist, the enhancement ratio was calculated on six different ROIs of the synovial membrane outlined by the operator: the wrist compartment, three extensor tendon compartments, and two flexor compartments. DCE-MRI results were quantitatively analyzed using the Dynamika software, a computer-aided semi-automated method. Contrast uptake dynamics such as maximum enhancement (ME), initial rate of enhancement (IRE), and a measure of the volume of inflammation (Ntotal ) were calculated. Results: Patients with RA had a higher number of tender (18.1±5.8 vs. 5.4±10.1; p=0.005) and swollen (14±5 vs 3±2.7; p<0.001) joints than those with PsA, but were similar for pain VAS (62.6±28 mm vs 44±26.6 mm; p=0.19) and C-reactive protein concentration (18.3±15.4 mg/dL vs 12.4±12.8 mg/dL; p=0.41). DAS28 CRP was 6.2±1 in RA and 3.7±1.4 in PsA (p=0.001). In PsA, the area of the ROI designed around the first and second extensor compartments was larger than in RA (p<0.001); the opposite was true for the extensor carpi ulnaris region (p<0.001). The volume of inflammation was significantly higher in RA than in PsA for all the extensor compartments, except the second, and in the joint synovial membrane (p=0.007). ME and IRE, the DCE-MRI indicators of the degree of inflammation, were higher for PsA in the joint synovial membrane (p=0.002 and p<0.001, respectively). There was a significant correlation between volume of inflammation, but not its degree, and DAS28 at the level of the wrist joint (r=0.6; p=0.01). Conclusions: Our preliminary data emphasizes the possibility to discriminate between different localizations and components of inflammation in the arthritic synovial membrane. No difference was observed in the volume and degree of inflammation between tenosynovitis and joint synovitis. MRI surface calculations highlighted the wrist synovial sheaths that are more frequently involved in PsA (1st and 2nd compartments of the extensor tendons) and RA (extensor carpi ulnaris). These significant differences in tendon compartment areas were independent from the activity of the included synovial membrane. In the synovial membrane of the wrist joint, the volume of inflammation was higher in RA but its degree was higher in PsA. This is particularly intriguing because disease activity, measured by DAS 28, was significantly higher in RA compared to PsA. It is possible that DAS28 is a surrogate of the amount of inflammation rather than of its intensity, as demonstrated by the significant direct correlation between DAS28 and Ntotal but not IRE and ME. Disclosure of Interest: G. Zampogna: None Declared, F. Barbieri: None Declared, M. Boesen: None Declared, F. Paparo: None Declared, O. Kubassova Shareholder of: Image Analysis, M. Parodi: None Declared, M. Cutolo: None Declared, M. Cimmino: None Declared